The correlation between EEG asymmetry and memory performance during semantic memory recall - Hanouneh, S. (Institute of Electrical and Electronics Engineers Inc., 2017)
The main objective of this research was to investigate the association between electroencephalogram (EEG) and semantic memory recall in human participant. A sample of 20 healthy participants was recruited and exposed to 10 minutes animated learning contents. After 30 minutes of the learning session, they performed a memory recall task; the correct and incorrect responses in recall task were recorded for computing the memory performance. EEG amplitude asymmetry was computed for six frequency band (delta, theta, alpha, beta, high beta, and gamma) and the correlation was checked with the memory recall. It was found that the EEG delta asymmetry correlated negatively (r=0.44-0.68; p-value<0.05) with the semantic memory recall in the right hemisphere (RH) more than left hemisphere (LH). In another hand EEG gamma asymmetry was also correlated negatively with the semantic memory recall (r=0.45-0.79; p-value <0.05) in RH more than LH. A positive correlation also was found in delta and gamma (r=0.47-0.56; p<0.05) these results suggested that the right hemisphere during semantic memory recall has high dynamic activity more than left hemisphere. © 2016 IEEE.